2021
DOI: 10.3390/ijerph18168245
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy Is Effective during Sleep in Preterm Infants

Abstract: Recent research found evidence supporting music therapy for preterm infants to stabilize vital signs and possibly promote neurodevelopment. Even though preterm infants spend a considerable amount of time sleeping, the effectiveness of music therapy during sleep has not been studied. The aim of this study was to investigate the effect of music therapy on preterm infants’ vital signs with respect to the state of wakefulness. The first 20 consecutive infants born with <32 weeks’ gestational age (GA) from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
(20 reference statements)
2
21
0
7
Order By: Relevance
“…Clinically stable patients received live music therapy from the second week of life twice per week until their hospital discharge [ 12 , 30 ]. The music therapist coordinated the timing of the individual therapy sessions with the nursing staff and parents in compliance with clinical routine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically stable patients received live music therapy from the second week of life twice per week until their hospital discharge [ 12 , 30 ]. The music therapist coordinated the timing of the individual therapy sessions with the nursing staff and parents in compliance with clinical routine.…”
Section: Methodsmentioning
confidence: 99%
“…Research investigating long-term effects of music therapy is only evolving [ 7 , 8 ] but vital sign responses to music therapy as a surrogate parameter of short term-stabilisation has been well-studied [ 9 , 10 , 11 ]. Currently, the optimal setting in which music therapy should be applied is under investigation [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these positive effects can already be observed during the intervention [ 10 ]. Live music therapy has a stabilizing effect on vital functions and is also effective during sleep [ 11 ]. It has recently been shown that live music therapy enhances the functional brain activity and even the brain structure in premature infants [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that music therapy without the voice has the same impact on the patient´s vital signs as other methods of MT, such as lullabies, conversations between parents and children, live music and the combination of other methods that stimulate the connection between parents and neonates. Among the methods of MT explored in other studies, it has been demonstrated that principally the HR shows changes under this adjuvant therapy [6,15,[18][19][20]. It is therefore understood that MT is an alternative therapy with signi cant results and that has the ability to bene t patients in the NICU.…”
Section: Discussionmentioning
confidence: 99%